2020
DOI: 10.1016/j.cpr.2020.101842
|View full text |Cite
|
Sign up to set email alerts
|

Reinforcement sensitivity, depression and anxiety: A meta-analysis and meta-analytic structural equation model

Abstract: Reinforcement Sensitivity Theory (RST) posits that individual differences in reward and punishment processing predict differences in cognition, behavior, and psychopathology. We performed a quantitative review of the relationships between reinforcement sensitivity, depression and anxiety, in two separate sets of analyses. First, we reviewed 204 studies that reported either correlations between reinforcement sensitivity and self-reported symptom severity or differences in reinforcement sensitivity between diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
70
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(82 citation statements)
references
References 359 publications
(185 reference statements)
8
70
3
1
Order By: Relevance
“…13 A recent meta-analysis found that BIS is a higher-order, shared factor for both depression and anxiety, whereas BAS is specific to depression. 14 In sum, extensive research has found that dysregulated BIS/BAS sensitivities play a critical roles in the development and maintenance of depression and anxiety. 15 However, to the best of our knowledge, relevant research is rarely conducted among older adults.…”
Section: Introductionmentioning
confidence: 99%
“…13 A recent meta-analysis found that BIS is a higher-order, shared factor for both depression and anxiety, whereas BAS is specific to depression. 14 In sum, extensive research has found that dysregulated BIS/BAS sensitivities play a critical roles in the development and maintenance of depression and anxiety. 15 However, to the best of our knowledge, relevant research is rarely conducted among older adults.…”
Section: Introductionmentioning
confidence: 99%
“…Second, we intended to analyze whether there would be significant differences based on reinforcement sensitivity measure. However, many studies (e.g., Gomez & Gomez, 2005;Harnett, Loxton, & Jackson, 2013) used more than one measure to assess reinforcement sensitivity. Owing to the dependency between measures' participant samples, subgroup analysis was inappropriate (Borenstein et al, 2009;H.…”
Section: Data Analytic Planmentioning
confidence: 99%
“…Indeed, it is possible that the relatively larger variances observed in the anxiety cluster reflect a real heterogeneity between the different anxiety disorders. Low positive affect, for example, has been found to be uniquely associated with social phobia (Naragon-Gainey et al, 2009;Watson, Clark, & Tellegen, 1988) and post-traumatic stress disorder (Nawijn et al, 2015), as compared to other anxiety disorders. This may reflect disorder-specific deficiencies of reward processing (Anderson & Hope, 2008).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gray & McNaughton, 2000). Dysregulated reinforcement sensitivity, on the other hand, is associated with a range of affective psychological disorders both crosssectionally and longitudinally (Bijttebier et al, 2009;Gonen et al, 2014;Johnson et al, 2003;Katz et al, 2020;Zald & Treadway, 2017;Zinbarg & Yoon, 2008). However, the role of reinforcement sensitivity in bipolar disorder is complicated by the fact that the two emotional poles of mania and depression are associated with opposing reinforcement sensitivity profiles.…”
mentioning
confidence: 99%